ANALISIS PENANAMAN PENDIDIKAN KARAKTER PROFIL PELAJAR PANCASILA DALAM KEGIATAN PRAMUKA DI SD NEGERI KARANGREJO 02 KOTA SEMARANG - Nikmatul Risa; Ikha Listyarini; Ragil Kristiawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to describe how character education for the profile of Pancasila students is implanted and the supporting factors and inhibiting factors for character education for the profile of Pancasila students in scout activities. This research method is qualitative research using a phenomenological approach. The research location was SD Negeri Karangrejo 02. The informants in this research were class III students and scout leaders. Based on the results of the research, it was concluded that the cultivation of Pancasila student profile character education in scout activities at SD Negeri Karangrejo 02 included: (1) Faithful devotion to God Almighty and noble character, (2) Global diversity, (3) Independence, ( 4) Working together, (5) Critical reasoning, and (6) Creative. The supporting factors in character education for Pancasila student profiles through scout activities at SDN Karangrejo 02 are (1) Religious basis, (2) Parental motivation, (3) Infrastructure, and (4) How to educate teachers. The factors inhibiting the character education of the Pancasila student profile in scout activities at SD Negeri Karangrejo 02 are: (1) Lack of support and attention from parents, (2) lack of interest from students, (3) Problems with the surrounding environment.